Intravitreal Enzyme Replacement Therapy Slows Retinopathy in Late Infantile Ceroid Lipofuscinosis Type 2 - Priglinger, Claudia S.; Courage, Carolina; Lotz-Havla, Amelie S.; Gerhardt, Maximilian; Ehrt, Oliver; Kurz, Matthias; Pudritz, Harald; Rudolph, Günther; Jackson, Christopher B.; Maier, Esther M. (Neuropediatrics, 2025)
Ceroid lipofuscinosis type 2 (CLN2) is caused by biallelic pathogenic variants in the TPP1 gene, encoding lysosomal tripeptidyl peptidase 1 (TPP1). The classical late-infantile phenotype has an age of onset between 2 and 4 years and is characterized by psychomotor regression, myoclonus, ataxia, blindness, and shortened life expectancy. Vision loss occurs due to retinal degeneration, usually when severe neurological symptoms are already evident.Intracerebroventricular enzyme replacement therapy (ICV-ERT) using recombinant human TPP1 (rhTPP-1) was shown to slow the neurological decline; however, it does not prevent loss of vision. Intravitreal rhTPP-1 (IVT-ERT) was described to halt retinal degeneration in a canine CLN2 model and a compassionate-use study in humans.We report on the clinical and ophthalmological outcome in an early-treated patient homozygous for a pathogenic variant in TPP1 known to be associated with severe CLN2 retinopathy.He was started on ICV-ERT at the age of 40 months and 4 weekly IVT-ERT in one eye at the age of 60 months. The other eye served as untreated control.Baseline best corrected visual acuity (BCVA) was 0.5 with mild bull's eye maculopathy evident in both eyes. After 24 months of IVT-ERT, BCVA in the treated eye was 0.2 with bull's eye maculopathy sparing outer retinal layers, whereas the untreated eye had progressed to endstage retinopathy and BCVA <0.02. No intraocular side effects occurred.Our results provide further evidence that IVT-ERT appears to be safe and markedly delays retinal degeneration preserving visual function and increasing the patient's quality of life, especially if started early.
Keywords: neuronal ceroid lipofuscinosis; ceroid lipofuscinosis type 2; intracerebroventricular enzyme replacement therapy; retinopathy; intravitreal enzyme replacement therapy; cerliponase alfa